2000
DOI: 10.3109/01674820009085588
|View full text |Cite
|
Sign up to set email alerts
|

To tell or not to tell - what parents think about telling their children that they were born following donor insemination

Abstract: Pioneering legislation regarding donor insemination was introduced in Sweden in 1985. The law gives the child, upon reaching sufficient maturity, the right to obtain information about the donor and his identity. One hundred and forty-eight Swedish couples with children conceived through donor insemination after the law was introduced have answered questions about disclosure and donation in a questionnaire. This article addresses the reasoning employed by individual couples in their decision whether or not to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 17 publications
2
48
0
9
Order By: Relevance
“…Almost all couples answered that they had not yet decided if they would tell their offspring about the mode of conception. Previous studies have shown that a majority of parents do not inform their children about the use of donor sperm, even when sperm from an identifiable donor has been used (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all couples answered that they had not yet decided if they would tell their offspring about the mode of conception. Previous studies have shown that a majority of parents do not inform their children about the use of donor sperm, even when sperm from an identifiable donor has been used (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Participation in gamete donation entails ethical as well as practical considerations; for instance, questions regarding disclosure of the donation to family members and donation offspring [3,4]. Therefore, clinic personnel constitute important informants and discussants concerning different aspects of oocyte and sperm donation.…”
Section: Introductionmentioning
confidence: 99%
“…Cook et al, 1995;Nachtigall et al, 1998;Lindblad et al, 2000) suggest that the main reason parents decide against openness is to protect the child from either the distress of discovering their father is not genetically related to them or of not being able to access genetic information about the donor. Secondly, parents wish to protect the father either from the child's potential rejection or from the social stigma associated with male infertility.…”
Section: Introductionmentioning
confidence: 99%